2020
DOI: 10.1111/jonm.13081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a person‐centred care intervention in an intensive care unit: Using mixed methods to examine nurses’ perspectives

Abstract: Aim We identified nurses’ experiences and changes in person‐ and family‐centred care (PFCC) after applying a family‐visiting programme in an intensive care unit (ICU). Background Critical care provision is shifting to include communication among patients, families and health care providers. Methods We used mixed methodology and a group pre‐ and post‐test design. In 2019, 30 ICU nurses completed an 8‐week programme, including keeping a diary and completing fundamental care activities. A survey of PFCC nursing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…According to this theory, the purpose of nursing is accomplished through human relationships via interpersonal processes, such as empathy, communication and interactions, which help narrow the gap between nursing theory and practice. General ward nurses in Korea are assigned over 10 patients, whereas ICU nurses care for two to four patients (Yoo & Shim, 2020 ). In COVID‐19 units, nurses are assigned fewer patients, and this seems to help them provide truly compassionate care.…”
Section: Discussionmentioning
confidence: 99%
“…According to this theory, the purpose of nursing is accomplished through human relationships via interpersonal processes, such as empathy, communication and interactions, which help narrow the gap between nursing theory and practice. General ward nurses in Korea are assigned over 10 patients, whereas ICU nurses care for two to four patients (Yoo & Shim, 2020 ). In COVID‐19 units, nurses are assigned fewer patients, and this seems to help them provide truly compassionate care.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning second theme, the ICU is a unique place where patients in critical condition must be separated from their families to focus on disease treatment fully. Visiting hours provide the only opportunity for patients and their families to meet (Beesley et al, 2018; Yoo & Shim, 2020). However, due to the negative perception of visitation among healthcare workers, patient protection and hospital policy in South Korea, families' desire to be involved in patient care is increasing, with restrictive visitation allowed only twice a day for an average of 30 min a day (Lee & Yi, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a Mixed methods study (Yoo & Shim, 2020) the results of the study found the number of monthly electives canceled due to unavailability of ICU beds, staff perceptions of intervention, sustainable contributing factors (Ros et al, 2021) and most nurses find the importance of nursing through an honest relationship with the ICU patient's family (Yoo & Shim, 2020). The results of the research are descriptive statistical studies, namely monitoring documentation is reported to result in a prominent care burden during intensive care.…”
Section: Study Characteristicsmentioning
confidence: 92%
“…Of the 10 included studies, three were conducted in Australia (Ros et al, 2021) (Riegel et al, 2021) (Tobiano et al, 2019), one in China (Qin et al, 2017), one in Belgium (Endacott et al, 2022), one in Sweden (Romare et al, 2022), one in the USA (Chapman et al, 2021), one in Egypt (Eltaybani et al, 2020), one in Korea (Yoo & Shim, 2020) and one in Saudi Arabia (Alhalal et al, 2020). The research design also varies, two are Mixed methods studies (Ros et al, 2021) (Yoo & Shim, 2020), two are descriptive statistics (Romare et al, 2022) (Tobiano et al, 2019), two are cross sectional (Riegel et al, 2021) (Alhalal et al, 2020), one is a descriptive case study (Qin et al, 2017), one is Delphi (Endacott et al, 2022), a single-center pre-and post-intervention design (Chapman et al, 2021) and one is qualitative (Eltaybani et al, 2020).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation